Pengaruh Media Flash Card Terhadap Kemampuan Memahami Nilai Sosial Kelas IV Sekolah Dasar Hang Tuah 10 Juanda - Nabilah Jihan Fadhilah; Apri Irianto; Reza Rachmadtullah (Indo-MathEdu Intellectuals Journal, 2023)
This research is motivated by students' lack of understanding of social values. Students' lack of ability to understand social values ​​is evident when students misbehave with other students, creating conflicts. The implementation of social values ​​is facilitated using flash card media, which can arouse students' interest and attention in learning social values. The purpose of this study was to determine the effect of flashcard media on students' understanding of social values ​​in fourth grade. This study uses a quantitative approach in a pre-experimental study using a single-group pre-test-post-test design. Fourth grade students participated in the current study, the sample of which was 20 children. The data collection method used was a test in the form of a pre-test, post-test and direct observation and documentation. Using a statistical analysis method with a formula is a paired sample test. Based on the results of the paired sample test, Sig (2-tailed) < 0.05 received a total of 0.000 < 0.05. Thus, when deciding for a paired sample test, one can conclude that h0 is rejected and ha is accepted. This means that it can be concluded that flashcard media affects the understanding ability of social values ​​of fourth grade students of Hang Tuah 10 Juanda Primary School